MO367USEFULNESS OF ECHOCARDIOGRAPHIC PARAMETERS IN LONG - TERM CARDIOVASCULAR EVENTS AFTER AN ACUTE KIDNEY INJURY EPISODE. (29th May 2021) - Cabrera, Alicia; Salanova Villanueva, Laura; Sanchez, Ana; Muñoz Ramos, Patricia; Ruano, Pablo; Quiroga, Borja
Abstract: Background and Aims: Acute kidney injury (AKI), a frequent condition during hospitalizations, leads to an increase morbidity and mortality. Cardiovascular events are one of the most post-AKI studied complications, but the role of the baseline functional and structural cardiac alterations on prognosis has not been widely studied. The aim of the present study is to evaluate the prognostic value of echocardiographic parameters in the incidence of cardiovascular events (CVE) after a hospitalization-acquire AKI. Method: In this is retrospective observational cohort study 1255 patients who presented AKI from 2013 to 2014 at our center were included. Baseline epidemiological data, comorbidities and echocardiographic parameters were collected. After discharge, patients were followed (mean 49±28 months) and post-AKI CVE were registered. In addition, new performed echocardiograms after discharge were collected. Associated factors to CVE and the predictive role of echocardiographic parameters were analyzed. Results: Among the 1255 included patients, 676 (54%) had a registered echocardiogram in the six months before the AKI episode. Of them, 231 patients (38%) had left ventricle hypertrophy (LVH), 178 (30%) pulmonary hypertension (PHT), 178 (30%) diastolic dysfunction and 138 (21%) systolic dysfunction. After discharge (and prior to post-AKI CVE), 248 (20%) patients had a new echocardiogram that revealed LVH in 108 patients (45%), diastolic dysfunction in 96 (42%), PHT in 68 (32%) and systolic dysfunction in 47 (19%). During follow-up, 484 (39%) patients had CVE. The presence of diastolic dysfunction, systolic dysfunction, PHT and LVH in any moment were associated factors to the incidence of CVE. An adjusted multivariate model showed that systolic dysfunction (hazard ratio [HR] 1.44, 95% confidence interval [95%CI] 1.073-1.943, p=0.015), age (HR 1.018, 95%CI 1.003-1.030, p=0.02), diabetes mellitus (HR 1.373, 95%CI 1.041-1.811, p=0.025), atrial fibrillation (HR 1.397, 95%CI 1.055-1.851, p=0.020) and diuretic intake (HR 1.580, 95%CI 1.171-2.131, p=0.003) were independent predictors of post-AKI CVE. Conclusion: The evaluation of cardiac structure and functionality valued by echocardiographic parameters can be a useful tool for stratifying CVE risk after an AKI. Systolic dysfunction is an independent predictor of post-AKI CVE.